2010
DOI: 10.1677/erc-10-0157
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin signaling activation patterns in neuroendocrine tumors of the lung

Abstract: Among alternative therapeutic strategies in clinically aggressive neuroendocrine tumors (NETs) of the lung, promising results have been obtained in experimental clinical trials with mammalian target of rapamycin (mTOR) inhibitors, though in the absence of a proven mTOR signaling activation status. This study analyzed the expression of phosphorylated mTOR (p-mTOR) and its major targets, the ribosomal p70S6-kinase (S6K) and the eukaryotic initiation factor 4E-binding protein 1 (4EBP1) in a large series of 218 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 40 publications
(44 reference statements)
3
61
0
1
Order By: Relevance
“…Our results agreed with the conclusions of the study conducted on 218 clinically malignant BP-NETs by Righi et al, who revealed a statistically significant higher expression level of p-mTOR in well-differentiated neuroendocrine tumors compared to high-grade carcinomas (29).…”
Section: Lesion Type P-akt Expression (No Of Patients) P-mtor Expressupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agreed with the conclusions of the study conducted on 218 clinically malignant BP-NETs by Righi et al, who revealed a statistically significant higher expression level of p-mTOR in well-differentiated neuroendocrine tumors compared to high-grade carcinomas (29).…”
Section: Lesion Type P-akt Expression (No Of Patients) P-mtor Expressupporting
confidence: 93%
“…Other studies have also investigated the p-AKT/p-mTOR pathway in BP-NETs, but their analysis of the percentage of immunoreactive tumor cells was combined with the staining intensity of the cells (26)(27)(28)(29). We decided to analyze our cases using only the percentage of positive cells, as our experience has indicated that the scoring system is highly subjective.…”
Section: Lesion Type P-akt Expression (No Of Patients) P-mtor Expresmentioning
confidence: 99%
“…However, an association of the activated mTOR pathway with a better patient prognosis has been reported (Noske et al 2008, Anagnostou et al 2009) as well. In one study on bronchial NETs, no prognostic impact of mTOR pathway components was reported (Righi et al 2010). We found that although mTOR expression itself was not associated with differences in patient prognosis, the detection of activated S6K confers a poor prognosis in stage IV midgut NETs.…”
Section: Discussionmentioning
confidence: 49%
“…These in vitro results are in line with our findings that mTOR expression as well as downstream activation of 4EBP1, eIF4E and S6K correlates with proliferation in GEP-NET. Most recently, in analogy to our work in GEP-NET, a large study on the expression of mTOR pathway components in lung NETs has been published in this journal (Righi et al 2010). The authors reported an overexpression of p-4EBP1 in high-grade tumours, in contrast to p-mTOR and p-S6K, which were strongly expressed in low-grade tumours.…”
Section: Discussionmentioning
confidence: 67%
“…Recent in vitro studies indicate that somatostatin receptors are overexpressed in metastatic typical carcinoid tumors of the lung [8] and that the mTOR is found in most lung NETs with higher expression in typical and atypical carcinoids (see Figure 3). [19].…”
Section: Management Of Advanced/metastatic Diseasementioning
confidence: 99%